TI_GERICHTE 12.2010.201 vom 9. März 2011 , Appalto, prescrizione quinquennale di lavori di artigiano, opere da piastrellista - TI Tribunale d'appello (2011)
Appalto, prescrizione quinquennale di lavori di artigiano, opere da piastrellista